Design, synthesis, chemical stability, packing, cyclic voltammetry, ionisation potential, and charge transport of [1]benzothieno[3, 2-b][1]benzothiophene derivatives. Issue 22 (5th May 2016) - Ruzié, Christian; Karpinska, Jolanta; Laurent, Anne; Sanguinet, Lionel; Hunter, Simon; Anthopoulos, Thomas D.; Lemaur, Vincent; Cornil, Jérôme; Kennedy, Alan R.; Fenwick, Oliver; Samorì, Paolo; Schweicher, Guillaume; et al.
Abstract : Unexpected effect of structure on electronic propeties. Abstract : Five new molecular semiconductors that differ from dioctylbenzothienobenzothiophene, by the introduction of ether or thioether side chains, have been synthesized and obtained in good yields. Their availability in sufficient quantities has allowed investigation of their electrochemical behaviour in solution and their electronic properties in solid state. Both ether and thioether compounds oxidise rather easily in solution, but nevertheless, they exhibit rather high ionisation potentials. This is a consequence of their crystal structure. Dioctylthioetherbenzothienobenzothiophene is rather sensitive to oxidation and degrades easily in close to ambient conditions. Dioctyletherbenzothienobenzothiophene is more stable. Its charge carrier mobility remains however rather moderate, on the order of 0.5 cm 2 V −1 s −1, whereas that of dioctylbenzothienobenzothiophene reached 4 cm 2 V −1 s −1, in the same conditions. The difference is explained by intrinsic factors as shown by a theoretical modelling.